STUDIES ON FOOD AND FEEDING HABITS OF CATFISH TACHYSURUS TENUISPINIS (DAY) - Mojumder, P; Dan, S S (Indian Journal of Fisheries, 2011)
It is observed that 37% of the food of Tachysurus teniiispinis, consists of crabs, prawns, Squilla sp and orustacesn remains; 26% polychaetes, 6.5% molluscs, 6.3% teleosts, 4.2% ophiuroids and the rest miscellaneous food items. T. tenuispinis is, therefore, a carrtivorous bottom feeder. As a single food item, polychaetes are most preferred. The fTuctuations in the intensity of feeding (points) and the volume of stomach contents (ml) in different months generally showed similar trends both in the small (less than 27.5 cm total length) and large (more than 27.5 cm total length) catfish. The relative importance of various food items during different months shows that feeding is selective